A full permutation polygon synthetic indicator (FPPSI) approach for measuring and evaluating city prosperity: case study in Da Nang City, Vietnam - Truong, Van Canh; Le, Ngoc Hanh; Tran, Thi An (Bulletin of Geography. Socio-economic Series, 2023)
Economic growth has dominated development strategies and goals for many years, but prosperity encompasses more than that. In 2013, UN-Habitat proposed the City Prosperity Initiative (CPI) as a tool to quantify cities' prosperity and sustainable development. The CPI is accompanied by six essential components with 62 indicators associated with the urban settlement, incorporating productivity, infrastructure development, quality of life, social inclusion, environmental sustainability, and urban governance and legislation. The research aims to use the indicators of CPI and adopted the Full Permutation Polygon Synthetic Indicator method to measure and evaluate the level of prosperity of Da Nang City of Vietnam with data from 2004 to 2019. According to the findings of our study, the value of a synthetic indicator for the prosperity of Da Nang City increased, from 0.34 in 2004 to 0.36 in 2009, 0.43 in 2014, and 0.45 in 2019, which indicates a moderate level of wealth. On the one hand, Da Nang City has high levels of quality of life, equity and social inclusion, and urban governance and legislation. However, the city still has modest determinants of prosperity in terms of the environment, productivity and infrastructure. The Full Permutation Polygon Synthetic Indicator technique provides a comprehensive solution that illustrates the system integration idea. As a result, the proposed methodology offers a potential foundation for decision-making to promote sustainable urban development strategies and assess the effectiveness of these actions